Meaning in Life After the Death of a Father Among Members of the Indonesian National Police (Polri): A Phenomenological Study - Ega Abinowo Herlambang; Fathana Gina; Ditta Febrieta (Journal of Health and Multidisciplinary Health Studies, 2026)
The death of a father is a significant life event that can profoundly affect an individual's psychological well-being and influence the way meaning in life is constructed. Beyond eliciting emotional responses, paternal loss may alter personal values, life goals, and self-understanding. This study aimed to explore the meaning of life following the death of a father among members of the Indonesian National Police (Polri). A qualitative phenomenological approach was employed. The participants were two police officers who experienced the death of their fathers during emerging adulthood and had lived with the loss for more than one year. Data were collected through semi-structured in-depth interviews and analyzed using Braun and Clarke’s thematic analysis. Four major themes emerged: the father as a source of values and life direction, the experience of loss as a life-disrupting event, acceptance as a process of transformation and responsibility-taking, and professional commitment as a source of new meaning. The findings indicate that meaning in life develops through a process of meaning reconstruction involving acceptance of loss, the development of new responsibilities, personal growth, and the integration of paternal values into both personal and professional life. Professional roles as police officers also contributed to maintaining life purpose and strengthening participants' sense of meaning following paternal loss. This study contributes to the literature on bereavement, meaning making, and meaning in life within the context of law enforcement professions.